先阅读下列因式分解的过程,再回答所提出的问题:
例1:1+ax+ax(1+ax)=(1+ax)(1+ax)=(1+ax)2;
例2:1+ax+ax(1+ax)+ax(1+ax)2
=(1+ax)(1+ax)+ax(1+ax)2
=(1+ax)2+ax(1+ax)2
=(1+ax)2(1+ax)
=(1+ax)3
(1)分解因式:1+ax+ax(1+ax)+ax(1+ax)2+…+ax(1+ax)n= ;
(2)分解因式:x﹣1﹣x(x﹣1)+x(x﹣1)2﹣x(x﹣1)3+…﹣x(x﹣1)2003+x(x﹣1)2004(答题要求:请将第(1)问的答案填写在题中的横线上)
解:(1)1+ax+ax(1+ax)+ax(1+ax)2+…+ax(1+ax)n,
=(1+ax)(1+ax)+ax(1+ax)2+…+ax(1+ax)n,
=(1+ax)2+ax(1+ax)2+…+ax(1+ax)n,
=(1+ax)2(1+ax)+…+ax(1+ax)n,
=(1+ax)3+…+ax(1+ax)n,
=(1﹣ax)n(1+ax),
=(1+ax)n+1;
(2)x﹣1﹣x(x﹣1)+x(x﹣1)2﹣x(x﹣1)3+…﹣x(x﹣1)2003+x(x﹣1)2004,
=(x﹣1)(1﹣x))+x(x﹣1)2﹣x(x﹣1)3+…﹣x(x﹣1)2003+x(x﹣1)2004,
=(x﹣1)2(﹣1+x)2﹣x(x﹣1)3+…﹣x(x﹣1)2003+x(x﹣1)2004,
=(x﹣1)2(1﹣x)+…﹣x(x﹣1)2003+x(x﹣1)2004,
=(x﹣1)2005.